Internet of Things Security and Data Protection - Ziegler, Sébastien; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an overview of the most recent developments in Internet of Things (IoT) security and data protection. It presents the results of several international research projects addressing this topic from complementary angles. It starts by analyzing the main privacy and security threats on IoT, as well as the evolution of data protection norms, such as the European General Data Protection Regulation (GDPR), and their impact on IoT. Through a comprehensive and systematic approach, the contributors present new perspectives on IoT & Cloud Computing security requirements. They discuss the most recent approach to support trusted IoT, including new models of privacy risk assessment, labeling and certification, and contractual tools (such as Privacy PACT). Practical implementations, such as in the European Large Scale Pilots on IoT for Smart Cities (Synchronicity), are presented, explaining how they address security, privacy and data protection. Finally, innovative models tosecure IoT systems are presented for the network and end-nodes security, including network threats analysis. Shares results from several international research projects on IoT, cybersecurity, and privacy; Combines complementary expertise from top experts in IoT, security, and data protection; Provides a comprehensive view on how to protect IoT deployments and make them comply with the GDPR.
Chapter 1. Internet of Things Cybersecurity Paradigm Shift, Threats Matrix and Practical Taxonomy -- Chapter 2. Privacy and Security Threats on the Internet of Things -- Chapter 3. End-nodes Security -- Chapter 4. IoT & Cloud Computing: specific security & data protection issues -- Chapter 5. Network Threat Analysis -- Chapter 6. Evolution of Data Protection Norms and their Impact on the Internet of Things -- Chapter 7. GDPR Compliance Assessment from Crowdsourcing to GDPR Certification -- Chapter 8. Universal Privacy Risk Area Assessment Methodology -- Chapter 9. Towards Trustable Internet of Things Certification -- Chapter 10. Voluntary Compliance Commitment Tool for European General Data Protection Regulation -- Chapter 11. IoT Privacy & Security in Smart Cities -- Chapter 12. End-user Engagement, Protection and Education -- Chapter 13. User-Centric Privacy.
Keywords: Telecommunication; Data protection; Signal processing; Application software; Communications Engineering, Networks; Data and Information Security; Signal, Speech and Image Processing; Computer and Information Systems Applications